Carbon storage in recombinant Escherichia coli during growth on glycerol and lactic acid. Issue 12 (29th July 2014) - Weiner, Michael; Tröndle, Julia; Albermann, Christoph; Sprenger, Georg A.; Weuster‐Botz, Dirk
ABSTRACT A fed‐batch process was studied with lactate and glycerol supply in the growth phase and glycerol supply during L‐phenylalanine production with recombinant E. coli K‐12. Lactic acid feeding was necessary for growth because the genes encoding the PEP‐consuming pyruvate kinase isoenzymes (pykA, pykF) have been deleted. An unexpected glucose efflux (67.6 ± 2.3 mgGlucose gCDW−1) was measured after the cells were harvested and resuspended in a mineral medium for metabolic perturbation experiments. As the efflux prohibited the application of these experiments, characterization of intracellular carbon storage was necessary. Therefore, two genetically engineered strains (one lacking glycogen metabolism and another additionally lacking trehalose synthesis) were applied in the fed‐batch process. Trehalose synthesis and accumulation from lactate was clearly identified as the source for glucose efflux after cell harvest and resuspension. Cultivations of strains with active pyruvate kinase successfully identified lactate as the carbon source causing intracellular trehalose storage. The usage of glycerol as sole carbon source during the whole process enabled an improved process performance and inhibited trehalose accumulation. Overall, this setup allows the application of perturbation experiments. Biotechnol. Bioeng. 2014;111: 2508–2519. © 2014 Wiley Periodicals, Inc.